Análisis de la estructura y composición florística de un bosque de terraza media, comunidad Puerto Almendra, distrito San Juan Bautista, Loreto - Perú - Dávila Paredes, Dario (2023)
The main objective of this work was to analyze the structure and floristic composition of forest species, with emphasis on abundance, frequency, dominance and importance value index; complemented with floristic complexity and comparison of the horizontal and vertical structure, of the evaluated forest species, Puerto Almendra community. In five (5) plots, a total of 152 trees were registered, represented by 23 families, 43 genera and 64 forest species.